Foundational Telemedicine Workshop for First-Year Medical Students Developed During a Pandemic - Susannah Cornes; Jeffrey M. Gelfand; Brook Calton (Association of American Medical Colleges, 2021)
Introduction In response to the COVID-19 pandemic and the need for social distancing, medical education curricula across the country had to be quickly transitioned from in-person experiences to remote sessions. Simultaneously, use of telemedicine in clinical practice skyrocketed. Despite telemedicine expansion and the opportunity afforded to teach these skills virtually, many institutions lacked telemedicine curricula. Methods We developed and evaluated a foundational telemedicine workshop during a pandemic (158 students in 28 groups) guided by principles to maximize learner engagement during remote learning, including use of discrete, time-limited activities (self-assessment, templated group exercises, review of brief multimedia, and active role-play.) Results Students completed pre- and postsession surveys to assess session impact. Of 158 students, 92 (58%) completed the presession survey, and 36 (23%) completed the postsession survey. There was an increase in confidence in all areas, particularly in skills related to starting the encounter, minimizing barriers, and taking the medical history. Learners reported the physical examination content as more useful than any other area and valued the exemplar videos provided. Discussion The pandemic highlighted our own institution's need to develop telemedicine curricula to prepare medical students to provide this increasingly essential service. We developed a foundational telemedicine skills session that increased students' reported confidence in their telemedicine knowledge and skills. The session could be easily adapted by other schools interested in incorporating telemedicine into their preclerkship curriculum. Additional experiences providing opportunities to practice and receive feedback on telemedicine skills with standardized and real patients are warranted.